Do overconfident workers cooperate less? The relationship between overconfidence and cooperation in team production - Vanessa Mertins; Wolfgang Hoffeld (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
The tendency to underestimate others' relative performance compared to one's own is widespread among individuals in all work environments. We examine the relationship between, and the driving forces behind, individual overconfidence and voluntary cooperation in team production. Our experimental data suggest an indirect and gender-specific link: Overconfident men hold more optimistic beliefs about coworkers' cooperativeness than men who lack confidence, and are accordingly significantly more cooperative, whereas overconfidence, beliefs, and cooperativeness are not correlated in women.
Keywords: M52; J33; J16; J24; C91; 330; team production; public good; experiment; real effort; cooperation; gender; overconfidence; belief